STUDI KOMPONEN KIMIA PELEPAH SAWIT VARIETAS TENERA DAN PENGEMBANGANNYA SEBAGAI MODUL PEMBELAJARAN KIMIA - Arpinaini Arpinaini; Sumpono Sumpono; Ridwan Yahya (PendIPA Journal of Science Education, 2017)
This study aims to (1) determine the levels of the components of the Tenera variety of palm oil compounds including extractives, holocellulose, ? - cellulose, and lignin. (2) Analyze the utilization of the pulp of Tenera varieties as pulp raw materials based on their chemical components; (3) application of chemistry learning module to improving student learning outcomes. Determination of extractive substance content with TAPPI test methods Q: 204; lignin content T: 222; holocellulose Q: 9 levels and ?-cellulose content with TAPPI test methods T: 204. then lignin, holocellulose and ?-cellulose produced from the procedure were characterized by an IR spectrophotometer. The results of the study were module and implemented in ICHO students in SMAN 2 Kota Bengkulu. The data of the research results were analyzed by ANOVA test at 5% level. The results of the characterization of lignin, holocellulose and ?-cellulose with FTIR obtained a distinctive peak of the respective functional groups of the macromolecules. From the research also obtained the average value of chemical component content on the palm velvet varieties of tenera according to their part of base, middle, ends with mean for extractive substance 8.49%, 7,87%, 6,74%, lignin 20,7 %, 18.95%, 16.69%. holocellulose 81.57%, 80.33%, 79.24% and ?- cellulose 44.57%, 43.56%, 43.26%. Based on the results of the variance analysis, the difference in position (base, center, tip) on the palm oil of the tenera varieties on extractive, lignin, holocellulose and ?-cellulose substances has significant differences. Based on the chemical component classification of Indonesian wide wood leaf, sheep betera varieties of tenera in all three positions are used as pulp raw materials because they have moderate lignin content, high levels of Holocellulose and moderate levels of ?-cellulose. The result of module implementation in students there is a significant difference between pretest and posttest value. The use of modules in learning in science groups can improve student learning outcomes.